TcyR regulates L-cystine uptake via the TcyABC transporter in Streptococcus mutans - Kim, Jennifer (2012)
Streptococcus mutans, a primary dental pathogen, has a remarkable capacity to scavenge nutrients from the oral biofilm for its survival. Cystine is an amino acid dimer formed by the oxidation of two cysteine residues that is required for optimal growth, whereas S. mutans modulates l-cystine uptake via two recently identified transporters designated TcyABC and TcyDEFGH, which have not been fully characterized. Using a non-polar tcyABC-deficient mutant (SmTcyABC), here we report that L-cystine uptake is drastically diminished in the mutant, whereas its ability to grow is severely impaired under l-cystine starvation conditions, relative to wild type. A substrate competition assay showed that l-cystine uptake by the TcyABC transporter was strongly inhibited by dl-cystathionine and l-djenkolic acid and moderately inhibited by S-methyl-l-cysteine and l-cysteine. Using gene expression analysis, we observed that the tcyABC operon was up-regulated under cystine starvation. TcyABC has been shown to be positively regulated by the LysR-type transcriptional regulator CysR. We identified another LysR-type transcriptional regulator that negatively regulates TcyABC with homology to the B. subtilis YtlI regulator, which we termed TcyR. Our study enhances the understanding of l-cystine uptake in S. mutans which allows survival and persistence of this pathogen in the oral biofilm.